A lesser giant millipede from Tanzania (Diplopoda, Spirostreptida, Spirostreptidae) - Enghoff, Henrik (Zootaxa, 2024)
Archispirostreptus microgigas sp. nov. is described, based on a specimen from Tanzania, and compared with its congeners, especially A. gigas (Peters, 1855) and A. divergens Krabbe & Enghoff, 1978 which may be the closest relatives of the new species, based on a potential synapomorphy (a rounded lobe on the gonopod telopodite).